Opioid crisis: a public health concern in Colorado, United States - Adeyemi A. Adeosun (Inishmore Laser Scientific Publishing Ltd, 2019)
Opioids have become one of the leading substances abused across many cities in the United States (US), with opioid use disorder already a public health concern. Most of the opioid-related deaths are due to prescription medication. In 2017, opioid overdose was responsible for 560 deaths in Colorado, representing 5.8 deaths per 100,000 residents. Women and children are increasingly affected, implying a need for concerted efforts to address it. Despite an alarming rate of opioid crisis among pregnant women, direct health consequences, especially Neonatal Abstinence Syndrome (NAS), are not clearly covered by health insurance schemes in Colorado, which significantly affects care and overall public health response. In this paper, the impact of opioids on maternal and child health in Colorado is examined, with recommendations towards improving overall management response.